Comparación de los contenidos de oxalatos y nitratos en amaranto, acelga y espinaca - de Troiani, R. M.; Sanchez, T. M.; Reinaudi, N. (Semiárida, 2020)
Comparación de los contenidos de oxalatos y nitratos en amaranto, acelga y espinaca